PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU DALAM PELAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2017 - Romy Putra Adhitama, 14.05.52.0288; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2018)
The purpose of this research are for examine and analyze the effect of likuidity firm size, leverage and profitability on the timeliness of financial reporting at manufacture companies listed on the BEI 2014-2017. The sampling technique in this research use purposive sampling. The sample in this study using 508 data from 572 companies manufacture sector listed on BEI year 2014-2017. Analysis method is logistic regression. The result are : the liquidity and leverage are not significant on the timeliness of financial reporting, firm size and profitability positive affect on the timeliness of financial reporting. Keywords : Timeliness, Liqudity, Firm Size, Leverage, Profitability